1994
DOI: 10.1002/jccs.199400084
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclo[3.2.1]octenones as Building Blocks in Natural Product Synthesis (IV): Formal Synthesis of (±)‐Hydroxyloganin Aglucone

Abstract: A formal synthesis of (±)-hydroxyloganin aglucone from bicyclo13.2.1]octenone 1 is described. Ring opening of syn.8-(metbanesulfonyloxy)-I-phenyltbiotricyclo[4,2.1.0 3 . 1]non-4-en-2-one 14 with potassium hydroxide is the key reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In the synthesis of iridoid monoterpenes, construction of the cyclopenta[ c ]pyran ring system from a more stable cis -bicyclo[3.3.0]octene precursor in the final stage is an important strategy (Figure ). ,5c,d, Recently, we found that fulvene 9 undergoes a three-carbon annulation to afford diquinane 8 . We believe diquinane 8 is a potential intermediate for the synthesis of iridoid natural products.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In the synthesis of iridoid monoterpenes, construction of the cyclopenta[ c ]pyran ring system from a more stable cis -bicyclo[3.3.0]octene precursor in the final stage is an important strategy (Figure ). ,5c,d, Recently, we found that fulvene 9 undergoes a three-carbon annulation to afford diquinane 8 . We believe diquinane 8 is a potential intermediate for the synthesis of iridoid natural products.…”
Section: Resultsmentioning
confidence: 97%
“…Oxidation of the formyl group in 12 with silver oxide and subsequent esterification of the resulting hydroxy acid with diazomethane afforded hydroxy ester 13 in 92% yield. Since 13 was converted into loganin ( 2 ) previously, this work constitutes a formal total synthesis of racemic loganin ( 2 ). 4a,b
4
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ketone 6 was first transformed to thioether 9. On treatment with aqueous acid, 9 was converted to β-hydroxy ketone 10 , which then reacted with methanesulfonyl chloride in pyridine to give the corresponding mesylate 5 …”
Section: Results and Disscussionmentioning
confidence: 99%